Histopathological study on liver of mice during aspergillosis infection - Hussain, Hiba Thamir (Iraqi Journal of Science, 2022)
In this study ,the Aspergillus fumigatus histopathological activity on the mice livers during aspergillosis became more obvious. The total number of 40 male Albino swiss mice were randomly divided into 8 groups (Five mice/group). The 1st group were immunosuppressed , while the 2nd group are not immunosuppressed , and control mice were instilled nasally with Phosphate buffer saline and Tween 20 ( five mice / control). The mice were sacrificed after 7th , 14th and 21st day post infection. It was found that immunosuppressive treatments increase substantially the susceptibility of animals to infection by invasive aspergillosis, with higher progression of disease and earlier expression of inflammatory cells comparing with the non immunosuppresed mice,as the hepatic fungal colony has increased earlier and become more rapid than in the non- immunosuppressed mice, despite the fact that the initial doses which have been administered were identical in above models.